Electrophilic C(sp2)−H Borylation of Nonactivated and Deactivated Arenes with Pyramidal Boron Lewis Superacids - Osi, Arnaud; Neil, Baptiste; Niessen, Nicolas; Chardon, Aurélien; Volk, Julia; Berionni, Guillaume (Synthesis, 2025)
The electrophilic C–H borylation of unactivated and deactivated, electron-poor arenes is a challenging reaction even with the most electrophilic borenium-ion species. We now report the transition-metal-free borylation of a wide range of aromatics and polyaromatics with a pyramidal boron Lewis superacid from the 9-boratriptycene family. The mechanism of formation of a highly reactive pyramidal boron Lewis superacid and the origin of the slow and continuous release of this highly reactive borylation reagent in the presence of a Lewis base are reminiscent of the reactions of latent frustrated Lewis pairs with small molecules.
Keywords: Borylations; Boron Lewis superacids; Borylating reagents; Pyramidal boranes; Boratriptycenes; C–H borylation reactions